Physiological characterization of Typhlatya cave shrimps: linking habitat with aerobic metabolism - Chávez-Solís, Efraín M.; Díaz, Fernando; Paschke, Kurt; Re, Denise; Rosas, Carlos; Rodríguez-Fuentes, Gabriela; Tremblay, Nelly; Mascaró, Maite (Frontiers in Marine Science, 2022)
The anchialine environment is characterized by a vertical stratification of water masses with different salinities. Cave shrimps of the genus Typhlatya are widespread inhabitants of the aquifer in fresh, brackish, and marine groundwater. Here we describe physiological aspects of three of the most abundant and widespread Typhlatya species that thrive in the fresh and marine groundwater habitats of the anchialine ecosystem of the Yucatan Peninsula. The aerobic scope (AS) of Typhlatya mitchelli, Typhlatya pearsei and Typhlatya dzilamensis was estimated through induced physical activity, whilst monitoring protein carbonylation and lipid peroxidation (as indicators of cellular damage), lactate accumulation (as an indicator of anaerobic metabolism) and the antioxidant system response. The critical thermal limits (CTL) of all three species as an additional measure of physiological plasticity were also determined. Our results showed that metabolic rates, AS and CTL were similar amongst the two species that inhabit fresh groundwater habitats, and differed markedly from T. dzilamensis, a species typically found in marine groundwater. The antioxidant system response in all three Typhlatya species accompanied the levels of aerobic metabolism following physical activity. However, the large amount of GSH observed in T. dzilamensis may be indicative of an adaptive trait to a more heterogeneous environment. The differences observed among Typhlatya species reflect different physiological adaptations that correspond to the environmental heterogeneity of their natural habitats. Our results suggest that the marine groundwater species, T. dzilamensis, could be better prepared to respond to a naturally more heterogeneous environment, in contrast to Typhlatya mitchelli and Typhlatya pearsei which rarely face environmental clines in the fresh groundwater habitat. Our findings contribute to a better understanding of the consequences of environmental change on ecologically important species that are restricted to live in the aquifer.